Effectiveness of ASEAN WPS Localization through the Desa Damai Program of Wahid Foundation and UN Women in Indonesia - Nala Nourma Nastiti; Yusep Ginanjar; Disa Hanelia Putri (Insignia: Journal of International Relations, 2026)
In the field of international relations, gender integration and security have become increasingly important as global and national dynamics evolve. Women are often viewed as more vulnerable to gender-based violence in conflict settings, yet they also contribute significantly to reconciliation and community healing through their sensitivity and empathy. Globally, the Women, Peace, and Security (WPS) agenda was institutionalized through UN Security Council Resolution 1325 in 2000, emphasizing women’s roles in conflict prevention, peacebuilding, protection, and post-conflict recovery. At the regional level, ASEAN localized this agenda through the 2023 Regional Plan of Action (RPA), which outlines priorities, opportunities, and challenges for member states, involving authorities, women leaders, youth, traditional leaders, and civil society. Indonesia, as a key ASEAN member, has shown strong commitment to gender equality. A concrete initiative is the Peace Village program launched in 2017 through the partnership between UN Women and the Wahid Foundation. This research examines how ASEAN’s RPA is translated into local contexts and identifies challenges and enablers of effective WPS implementation.